Differences in the clinical presentations of anti-NMDAR (anti-N-methyl-D-aspartate receptor) encephalitis with status epilepticus: a retrospective case series - Sejahtera, Desin Pambudi; Satiti, Sekar; Mukhtar, Ishana Nafeeza; Andatu, Roshynta Linggar; Khairani, Atitya Fithri (Indonesian Journal of Biomedicine and Clinical Sciences, 2024)
Literature on anti-NMDAR (anti-N-methyl-D-aspartate receptor) encephalitis is limited in developing countries, including Indonesia. This retrospective observational case series explored the impact of early diagnosis and treatment on patient outcomes in four distinct cases of anti-NMDAR encephalitis with status epilepticus, and other related conditions, of patients referred to Dr. Sardjito General Hospital, Yogyakarta. Clinical data from May 2021 to August 2023 were collected through the review of medical records, encompassing demographic information, clinical presentation, history, laboratory results, imaging studies, EEG reports, interventions, and the progression of the disease. Four cases were reported, three of whom were diagnosed with anti-NMDAR and one with bacterial encephalitis, each presenting a variety of neuropsychiatric clinical symptoms, leading to hospitalization, extensive testing, and interventions to establish the definitive diagnosis. Cases 1 and 4 have a childhood history of seizures. The cases analyzed factors including the impact of childhood versus adulthood onset and the adherence to taking medicine regularly leading to exacerbation symptoms and relapses. Distinguishing anti-NMDAR encephalitis from related conditions, such as bacterial encephalitis, was further complicated in patients with varied neuropsychiatric presentations (seizures, hallucinations, irritable behavior, headaches) and responses to the treatment. Supporting investigation finds positive NMDAR testing and abnormal CT, MRI, and EEG results, contributed to definitive diagnoses. It could be concluded that comprehensive diagnostic investigations are important for prompt recognition of clinical characteristics, and early initiation of immunomodulatory therapy in managing anti-NMDAR encephalitis and related conditions in Yogyakarta, Indonesia.